Comparison of immunohistochemical characteristics of expression estrogen receptors-alpha, progesterone receptors, p16, p53, Ki-67 and caspase 3 in invasive endometrial adenocarcinoma of different grade. - Tumanskiy, V. A.; Chepets, A. V. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Endometrial cancer occupies the sixth place among newly diagnosed neoplasm in women each year. Objective. Immunohistochemical characterization of the expression of the estrogen receptors-α, progesterone receptors, p16, p53, Ki-67, caspase-3 by the cells of invasive endometrioid endometrial adenocarcinomas of various grade. Methods. The invasive endometrioid endometrial adenocarcinoma (stage pT1-4MxNxG1-3) in the uteruses of 56 perimenopausal women with the verified diagnosis of endometrial cancer were analyzed. For this purpose, immunohistochemical and morphometrical studies were used. Results. The expression levels of p16 and Ki-67 significantly reduce in the tumor cells (р<0,05). The caspase-3 expression level significantly increased in the tumor stromal cells with FIGO (International Federation of Gynecology and Obstetrics) grade increasing (p<0.05). The FIGO grade of the invasive endometrioid endometrial carcinoma has significant relations with the expression levels of the estrogen receptor-α (γ=-0,68), progesterone receptors (γ=-0,78), p53 (γ=-0,45 in the group of adenocarcinomas with low and high expression levels of p53; γ=0,75 in the adenocarcinomas group with overexpression of p53 ), p16 (γ=0,76), Ki-67 (γ=0,34), caspase-3 (γ=-0,84) in the tumor cells and estrogen receptor -α (γ = -0,36), caspase-3 expression levels in tumor stromal cells (γ = 0,84). Conclusion. With increasing of FIGO grade of the invasive endometrioid endometrial adenocarcinoma the sensitivity of tumor cells to regulatory signals of estrogen and progesterone decreases. The expression level of p16 increases, which indicates the violations of p16-associated cell cycle control mechanism. The proliferation level of tumor cell increases and the level of tumor cells apoptosis decreases.